2023
DOI: 10.1177/00178969231211853
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between COVID-related health literacy, mental health and workload of school leaders

Rune Müller Kristensen,
Kevin Dadaczynski,
Orkan Okan
et al.

Abstract: Objective: Studies have shown that school leaders’ health literacy is key to supporting health development in school. During the COVID-19 pandemic, the importance of school leaders’ health literacy became evident, as school leadership was characterised with uncertainty and demanded high levels of alertness to the need to implement rapidly changing health-related measures at short notice. This study sought to explore school leaders’ health literacy, mental health and work-related characteristics in Danish publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Understandably, intensive communication during school closures increased the workload for most school leaders in Kazakhstan, similar to international evidence (Bellemans et al, 2023;Kristensen et al, 2024). Although past research does not address the correlation between high work intensity and school types, location, and school leader gender, the current study reveals that urban school leaders faced a significant increase in their workload compared to their rural counterparts.…”
Section: Practices Of Parental Engagement and Work Intensitysupporting
confidence: 74%
See 2 more Smart Citations
“…Understandably, intensive communication during school closures increased the workload for most school leaders in Kazakhstan, similar to international evidence (Bellemans et al, 2023;Kristensen et al, 2024). Although past research does not address the correlation between high work intensity and school types, location, and school leader gender, the current study reveals that urban school leaders faced a significant increase in their workload compared to their rural counterparts.…”
Section: Practices Of Parental Engagement and Work Intensitysupporting
confidence: 74%
“…Firstly, while previous international literature has highlighted how teachers' insufficient digital competence impacted the effectiveness and frequency of online lessons during school closures (Ko¨nig et al, 2020;Lepp et al, 2021), the current study extends our understanding of how school leaders addressed this issue by supporting teachers' digital literacy and navigating disparities in professional development opportunities. Secondly, while prior international research has recognized the significance of maintaining regular lines of communication with stakeholders, including parents (McLeod & Dulsky, 2021), resulting in school leaders' workload intensity (Bellemans et al, 2023;Kristensen et al, 2024), the current study has identified the unequal distribution of the burden of intensive communication among school leaders. Thirdly, while existing literature has touched on teacher autonomy in academic matters during the pandemic (Azhari & Fajri, 2022;Chang et al, 2022;Keese et al, 2022;Kramer et al, 2023), this study examined the intersection of leadership practices regarding autonomy with school type, location, and school leaders' gender.…”
Section: Study Strengths and Limitationsmentioning
confidence: 89%
See 1 more Smart Citation